The The Effect of Picture Media in Improving Arabic Mufradāt in Arabic Language Participants of Universiti Islam Selangor, Malaysia - Safira Aulia; Al Anshory, Abdul Muntaqim; Nur Hasaniyah; bin Mat Noradin, Muhammad Farhan (Program Studi Pendidikan Bahasa Arab (PBA), Universitas Islam Negeri Datokarama Palu, 2025)
Abstract The aim of this study is to determine whether visual media influences the improvement of Arabic language skills among participants of the Arabic language camp at the Islamic University of Selangor, Malaysia. Vocabulary mastery is a crucial foundation in Arabic language learning, as it determines one’s ability to understand and communicate effectively. This research employed a quantitative approach with a quasi-experimental design, where participants were divided into two groups: an experimental group taught using visual media and a control group taught through the lecture method. Data collection was conducted using pre-tests and post-tests. The results of the independent t-test analysis showed a statistically significant difference between the average scores of the two groups. The experimental group demonstrated a significantly higher average score compared to the control group. The calculated t-value was 6.184, which exceeded the critical t-value of 2.021 at the 0.05 significance level, with a two-tailed significance of 0.001. These results indicate that the null hypothesis is rejected and the alternative hypothesis is accepted, meaning that the use of visual media positively influences the improvement of Arabic vocabulary. These findings contribute significantly to the development of more effective and engaging Arabic language teaching strategies.